Epidemiology and determinants of dyslipidemia in Iranian population: Results from the PERSIAN cohort - Nazgol Motamed-Gorji; Sadaf G. Sepanlou; Marjan Moallemian Isfahani; Ali Ahmadi; Meysam Alipour; Azizallah Dehghan; Pedram Ebrahimnejad; Mohhamad Reza Fattahi; Masoumeh Goddusi Johari; Zahra Jamali; Mahmoud Ali Kaykhaei; Seyyedadel Khoshbou_Garebagh; et al. (PLoS ONE, 2026)
Background Dyslipidemia is one of the main risk factors for cardiovascular diseases worldwide. The current study aimed to determine the prevalence and correlates of dyslipidemia in Iran, in addition to factors associated with receiving treatment and attaining treatment goals. Methods The current study used the data of a very large cross-sectional survey, Prospective Epidemiological Research Studies in IrAN (PERSIAN), including 163,770 Iranians aged 35–70 years from 18 distinct areas across Iran, between 2014 and 2020. Participants’ characteristics were recorded using validated questionnaires including biological samples, physical measurements, and self-reported information. Dyslipidemia was defined according to the Third Report of the Adult Treatment Panel. Triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL) and low-density lipoprotein (LDL) were measured as components of dyslipidemia. We calculated participants’ 10-years cardiovascular risk using the World Health Organization risk charts to assess the eligibility for treatment and achievement of control. Multivariable logistic regression analyses were conducted to investigate the correlates of dyslipidemia, receiving treatment, and control. Results The mean age of participants was 49.4 (±9.1) years, among whom 55% were women and 70% were urban residents. The weighted prevalence of dyslipidemia was 73.2% (95% CI: 71.5–75.0%). High TG (40.4%, 36.9%−44.4%) and high TC (36.2%, 32.9%−39.4%) comprised the most prevalent components of dyslipidemia, followed by low HDL-C (32.1%, 25.8%−38.4%), high non-HDL-C (26.6%, 24.0%−29.1%), and high LDL-C (23.4%, 21.1%−25.7%). In multivariable logistic regression analysis, younger age, tobacco consumption, low physical activity, high BMI, diabetes, and hypertension were associated with low HDL-C and high TG. Older age, alcohol consumption, low physical activity, and high BMI were associated with high TC and high LDL-C. Women had higher likelihood of having abnormal levels for all components of dyslipidemia, except for high TG. Older age, high wealth score, high BMI, and low physical activity were associated with higher utilization of statin treatment. Good lipid control in those who were treated with statin was higher in males and diabetics. Conclusion The prevalence of dyslipidemia in Iranian population is extremely high, and certain groups are at higher risk of poor lipid control. Findings of this study highlight the necessity of developing a national guideline for management of dyslipidemia.